Anodic Reactions and the Corrosion of Copper in Deep Eutectic Solvents. Issue 9 (30th May 2018) - Green, T. A.; Valverde, P.; Roy, S.
Abstract : An analysis of the anodic reaction occurring at soluble copper anodes during the electrodeposition of copper from an ethaline-based deep eutectic solvent (DES) has been performed. It was shown by UV-Vis spectroscopy and electrochemical measurements that the dominant anodic species produced is the CuCl2 − complex. In pure ethaline the current efficiency of the anodic process is 100% and the dissolution valency is one. However, in the presence of Cu(II) species the apparent dissolution valency measured gravimetrically was typically less than unity, corresponding to an observed mass loss greater than that expected from Faraday's law. Moreover, the apparent dissolution valency showed a marked dependence on the electrode rotation rate, Cu(II) concentration and the water content of the deep eutectic solvent. These observations were consistent with a corrosion reaction occurring in parallel with anodic dissolution. The most likely corrosion process is the comproportionation reaction: CuCl4 2− + Cu → 2CuCl2 − . Voltammetric data indicate that the rate of this process is controlled by the mass transport of the CuCl4 2− complex to the surface and can readily explain the observed dissolution valency dependencies. Finally, it is noted that complex dissolution of Cu anodes in deep eutectic solvents makes their implementation as soluble anodes problematic.